Mycophenolic acid derivative 118 improves outcome of skin grafts by suppressing IL-17 production - Kong Fang-yuan; Chen Wei; He Shi-jun; Lin Ze-min; Li Xin; Zhang Xiao-hui; Yang Xiao-qian; Zhu Feng-hua; Tong Xian-kun; Zhou Yu; Tang Wei; Duan Wen-hu; et al. (Acta Pharmacologica Sinica, 2016)
Fang-yuan KONG1, #, Wei CHEN1, #, Shi-jun HE1, Ze-min LIN1, Xin LI1, Xiao-hui ZHANG1, Xiao-qian YANG1, Feng-hua ZHU1, Xian-kun TONG1, Yu ZHOU1, Wei TANG1, *, Wen-hu DUAN1, *, Jian-ping ZUO1, 2, * 1State Key Laboratory of Drug Research, Shanghai Institute of Materia Medica, Chinese Academy of Sciences, Shanghai 201203, China; 2Laboratory of Immunology and Virology, Shanghai University of Traditional Chinese Medicine, Shanghai 201203, China Aim: To investigate the effects and underlying mechanisms of 118, a novel derivative of mycophenolic acid, in a murine allogeneic skin graft model. Methods: Skin grafts were conducted by grafting BALB/c donor tail skin into C57BL/6 skin beds (allograft) or by grafting female C57BL/6 donor tail skin into female C57BL/6 skin beds (syngraft). The mice were treated with the derivative 118 (40 mg·kg-1·d-1, po) for 13 d (3 d before and 10 d after transplantation). Skin grafts, splenocytes and graft-infiltrated lymphocytes were isolated and examined ex vivo. The effects of the derivative 118 on naive CD4+ T cell differentiation were examined in vitro. Results: Treatment with the derivative 118 dramatically increased the survival rate of murine allogeneic skin grafts. Flow cytometric analysis and H&E staining showed that the derivative significantly decreased inflammatory cell infiltration into the grafts. The levels of the chemokines CXCL1, CXCL2, CCL7, and CCL2 were reduced in the derivative 118-treated grafts. Additionally, the derivative 118 significantly suppressed the IL-17 levels in the grafts but did not affect the differentiation of systemic helper T cells in the murine allogeneic skin graft model. Furthermore, IL-23p19 expression was suppressed in the grafts from the derivative 118-treated group, which might be due to decreases in TLR4 and MyD88 expression. Finally, the derivative 118 did not exert direct influences on helper T cell differentiation in vitro. Conclusion: Treatment with the mycophenolic acid derivative 118 improves murine allogeneic skin grafts by decreasing IL-23 expression and suppressing local IL-17 secretion in the grafts, rather than directly inhibiting Th17 differentiation. Keywords: mycophenolate mofetil; derivative 118; transplantation; skin graft; allograft; syngraft; IL-17; IL-23 This work was supported by grants from the National Natural Science Foundation of China (NSFC)(Nos 81072652, 81273524, and 81273525). # These authors contributed equally to this work. * To whom correspondence should be addressed. E-mail jpzuo@mail.shcnc.ac.cn (Jian-ping ZUO); whduan@mail.shcnc.ac.cn (Wen-hu DUAN); xwhduan@mail.shcnc.ac.cn (Wei TANG) Received 2012-11-13 Accepted 2013-02-07